FLOOD CONTROL THROUGH STRUCTURAL AND NON-STRUCTURAL AMPLIFICATION APPROACHES - Sebastian, Ligal (Jurnal Teknik Sipil, 2022)
Changes in land use along with the increase in population both in urban and rural areas, of course, are followed by problems and environmental damage, for example; flooding, garbage, and damage to drainage construction. Preventing flood disasters, it is necessary to develop strategies and control techniques for flood-affected areas (including watersheds) through structural and non-structural amplification strategies in their control. The method of approach is qualitative description and descriptive comparative case which aims to look at the flood problems that occurred in several locations from a technical and social point of view as well as strategies for handling them. In addition, a spatial analysis of the watershed area was carried out on field observation data on objects affected by flooding to determine the physical and social conditions related to flood control efforts. The government has taken various steps to overcome flooding, but it is recognized that it is still not optimal due to land suitability factors. Through structural and non-structural amplification approaches, watershed conditions can be evaluated and optimized over time according to conditions. Structural and non-structural amplification approaches are predicted to help the process of flood prevention and control more optimally. The concept of evaluating land suitability for residential areas and watershed areas, as well as the social conditions of local communities.